An advance encryption standard cryptosystem in IoT transaction - Zolidah Kasiran; Shapina Abdullah; Normazlie Mohd Nor (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
IoT create an ecosystem that can be useful to the world with its various services. That make the security of IoT is more important. This paper presents a proposed technique to secure data transaction from IoT device to other node using cryptography technique. AES cryptography and IoT device model ESP8266 is used as a client to send data to a server via HTTP protocol. Security performance matrices used eavesdropping attack with Wireshark sniffing and brute-force attack. will be simulated to the proposed method in order to ensure if there is any possibility it can be cracked using those attacks and to evaluate the performance of ESP8266, several experiments were be conducted. Result gather from this experiment was evaluated based on processing time to see the effectiveness of the platform compare to different data size used while adapting this technique.